1993
DOI: 10.1136/thx.48.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Moraxella catarrhalis in a respiratory unit.

Abstract: The clinical and epidemiological features of an outbreak of nosocomial Moraxella catarrhalis infection in a respiratory unit are described. Six isolates from five patients were shown to be indistinguishable by immunoblotting and restriction endonuclease analysis and different from 11 other, unrelated clinical strains. (Thorax 1993;48:91-92) Central Microbiological Laboratories

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 3 publications
0
31
0
1
Order By: Relevance
“…Most of these outbreaks involved respiratory tract infections and some occurred exclusively in pulmonary units [10,12,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these outbreaks involved respiratory tract infections and some occurred exclusively in pulmonary units [10,12,31].…”
Section: Discussionmentioning
confidence: 99%
“…McLeod et al [11] reported that 43 of 81 patients (53%) with M. catarrhalis infection were infected in a hospital and that the infection was associated with the proximity of the patient to other patients. Most nosocomial infections with M. catarrhalis involve the respiratory tract and outbreaks have been reported in respiratory units and paediatric intensive care units [10,12].…”
mentioning
confidence: 99%
“…M. catarrhalis has also been implicated as an important cause of respiratory disease in adults with predisposing conditions (41). Studies from several centers have reported clusters of nosocomial outbreaks of M. catarrhalis, most of which occurred in pulmonary care units (43,45). Although multiple studies have described specific bacterial components considered potential virulence factors, the steps involved in the pathogenesis of M. catarrhalis colonization and infection remain elusive (28,41).…”
mentioning
confidence: 99%
“…Preliminary observations involving typing of strains indicate that some of the clusters involved infections with several distinct strains of B. catarrhalis (13,121). Other studies implicate person-to-person transmission and suggest that hospital personnel may be involved in transmission (135,144). Analysis of strains from outbreaks by newly developed typing methods will be important in elucidating the factors responsible for nosocomial outbreaks so that rational strategies for prevention can be implemented.…”
Section: Nosocomial Infectionmentioning
confidence: 99%
“…The most widely used method to type strains of B. catarrhalis to date has been restriction endonuclease analysis of genomic DNA (44,45,58,89,118,121,134,135,144). More recently, a more refined form of restriction endonuclease analysis involving pulsed-field gel electrophoresis of large fragments of genomic DNA has been developed (99,102).…”
Section: Genotype-based Typing Systemsmentioning
confidence: 99%